Penerapan Terapi Social Skills Training Pada Klien Isolasi Sosial dengan Pendekatan Teori Dorothy E. Johnson Behavioral System Model di Kelurahan Balumbang Jaya Kecamatan Bogor Barat Kota Bogor : Application of Social Skills Training Therapy in Social Isolation Clients with the Dorothy E. Johnson Behavioral System Model Theoretical Approach in Balumbang Jaya Village, West Bogor District Bogor City - Sutejo (Fakultas Keperawatan Universitas Andalas, 2013)
Prevalence of mental disorders has increase significantly each year. The intervention is not only foccus in hospital, but also in community that called community mental health. Heavy mental disorders that often happened is schizophrenia, in wich the client has failed to do social function, failed to cope interpersonal skill problems, have poor social skills, and have deficit cognitif function. This scientific paper is aim to have description about application of social skill training therapy to the client with social isolated through the ability to interacting to others utilizing Behavioral System Model approach. The amount of clients is 13 of 38 mental disorders client. The result is client able to show improvement in verbal and non verbal communication and also able to interacting to others around. The recommendation of this scientific paper is nurse have competency to apply social skills training to client with social isolated and the importance to have mental health nurse specialist in community area.